Reduced lung function both before bronchiolitis and at 11 years. Issue 5 (1st November 2002) - Turner, S W; Young, S; Landau, L I; Le Souëf, P N
Abstract : Background and Aims: We have previously shown an association between reduced premorbid lung function (V'maxFRC) and bronchiolitis. We hypothesised that individuals with bronchiolitis will go on to have reduced lung function and increased respiratory symptoms in childhood. Methods: V'maxFRC was measured at 1 month of age; individuals with bronchiolitis were prospectively identified. Annual symptom questionnaires were completed from 3 to 6 years. At 11 years of age, children underwent an assessment including questionnaire, lung function, airway response to histamine (AR), and skin prick testing. Results: Eighteen individuals with bronchiolitis were ascertained from 253 cohort members. Children with bronchiolitis had increased viral induced wheeze at 3 (OR 5.8, 95% CI 1.4 to 25.2; n = 103) and 5 years (OR 5.3, 95% CI 1.1 to 25.5; n = 101). At 11 years of age, 194 children were assessed including 16 with past bronchiolitis. These 16 individuals had reduced mean z scores for % V'maxFRC compared with other children (−0.56 and 0.06 respectively) and mean z scores for % FEF25–75 at 11 years (−0.53 and 0.06 respectively). At 11 years, FEV1, FVC PEF, AR, atopy, wheeze, and diagnosed asthma were not different between groups. Conclusions: Reduced lung function is present before and after bronchiolitis; the level of reduction is comparable. The mechanism for wheeze and reduced lung function after bronchiolitis appears to be related to premorbid lung function and not bronchiolitis per se.